(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Nephrotic syndrome (NS) is the most common glomerular disease seen in the pediatric age group. Objective: To study demographic, socioeconomic, disease related characteristics and the physical examination including height, weight and blood pressure correlation with frequency of relapses in children with steroid sensitive NS (SSNS). Methods: This is a cross sectional study that was conducted at Nephrology Consultation Clinic, in Al-Imamein Al-kadhimein (peace on them) Medical City, Baghdad, Iraq starting from 1st of January, 2020 to 31 July, 2021. Results: Total number of patients was 60 children with SSNS, 24 (40%) patients were frequent relapsers and 36 patients (60%) were infrequent relapsers. Most of the children at onset of the disease were less than 5 yr (76.7%) and males were more than females (78.3%). Fifty-three patients were responder to steroid in less than 2 weeks (88.3%). Ten patients with low body weight (16.7%) and 6 patients with low body height (10%), 25 patients presented with elevated blood pressure (41.7%). A significant correlation was found between future relapses and following characteristics; response to steroid in less than 2 weeks, urinary tract infection (UTI) and gross hematuria, low body weight, short stature and elevated blood pressure. Conclusion: Comparing frequent with infrequent relapsers, the following factors found to be statically significant: response to steroid less than 2 weeks, UTI, gross hematuria, low body weight, short stature and elevated blood pressure. Keywords: Relapse, steroid, nephrotic syndrome, frequency Citation: Ali SH, Ali HA, Neamah AM. Risk factors for relapses in children with steroid sensitive nephrotic syndrome. Iraqi JMS. 2022; 20(2): 226-232. doi: 10.22578/IJMS.20.2.9